Mengukur Tingkat Kesiapsiagaan Anggota PKK RT. 05 Desa Banyuraden dalam Menghadapi Bencana Gempa - Restu; Mandiyo Priyo (Universitas Lancang Kuning, 2020)
Women as agents of change are expected to have an active role in disaster risk reduction (DRR) activities, mainly to defend themselves and their families from the effects of disasters. This dedication activity is a preparedness level assessment of the members of PKK RT. 05 RW. 08, Banyuraden village, Gamping Sleman DIY. It is an academic involvement to support the village program in realization a disaster-resilient village (Destana) and to solute the partner's problem. The assessment method uses a framework developed by the Indonesian Institute of Sciences (LIPI) in collaboration with The United Nations Educational, Scientific and Cultural Organization (UNESCO) and International Strategy for Disaster Reduction (ISDR) in 2006. There are three stages of assessment, i.e. a survey for collecting data using a questionnaire, analyzing the preparedness index, and determining the preparedness level. Because the activities were carried out during the Covid-19 pandemic, the questionnaire was conducted using Google forms to implement the physical distancing program. This dedication activity found a description that the members of PKK RT. 05. RW. 08 Banyuraden village, Gamping Sleman DIY has a moderate of preparedness rate, with an index of 62.07%. The aspect of disaster knowledge was classified as good, but the emergency response plan and resource mobilization are not yet. The implementation of the Destana program in the Banyuraden village, Sleman district, especially in RT.05 RW.08 might be aligned with the results of this dedication activity. Further dedication activities can also be carried out, such as drafting emergency response plans and organizing preparedness training for families to improve the community preparedness of RT. 05 RW. 08, Banyuraden, Gamping Sleman DIY.